Romance and pleasure : understanding the sexual conduct of young people in Dhaka in the era of HIV and AIDS - Lazeena, Muna (University Press, 2005)
On the sexual behaviour of young adults in Dhaka, Bangladesh and the possibilities of HIV infections due to unsafe sex; a study.